DIFFERENCES IN THE TYPES OF PRONUNCIATIONS IN DIALECTS ON THE EXAMPLE OF THE SOUTHERN SAMPLE OF THE NORMS OF EXPRESSIONS IN INDIA ON THE EXAMPLE OF THE USE OF WORD-FORMING ELEMENTS OF THE LEXICAL VARIETIES "TAMIL" AND "URDU" IN MODERN COLLOQUIAL ENGLISH - Абушаев Амир Камилевич (Journals Park Publishing, 2022)
Differences in the types of pronunciations in dialects on the example of the southern sample of the norms of expressions in India on the example of the use of word-forming elements of the lexical varieties "Tamil" and "Urdu" in modern colloquial English
Keywords: development, examples, combinations, language elements, tribes, Urdu language, community, innovative examples.